2010
DOI: 10.1007/s10803-010-0992-0
|View full text |Cite|
|
Sign up to set email alerts
|

Prenatal and Perinatal Risk Factors for Autism in China

Abstract: We conducted a case–control study using 190 Han children with and without autism to investigate prenatal and perinatal risk factors for autism in China. Cases were recruited through public special education schools and controls from regular public schools in the same region (Tianjin), with frequency matching on sex and birth year. Unadjusted analyses identified seven prenatal and seven perinatal risk factors significantly associated with autism. In the adjusted analysis, nine risk factors showed significant as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
148
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 63 publications
10
148
2
2
Order By: Relevance
“…Varying reports have also implicated measles and mumps (Deykin and MacMahon, 1979), cytomegalovirus (Libbey et al, 2005), polyomaviruses (Lintas et al, 2010), and influenza (Atladottir et al, 2012;Deykin and MacMahon, 1979;Shi et al, 2003;Zhang et al, 2010) in the incidence of ASD. Some studies suggest fever as a correlate (Atladottir et al, 2012), with this risk potentially tempered by anti-fever medications, such as Advil, Tylenol, or Nyquil (Zerbo et al, 2013).…”
Section: Congenital Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varying reports have also implicated measles and mumps (Deykin and MacMahon, 1979), cytomegalovirus (Libbey et al, 2005), polyomaviruses (Lintas et al, 2010), and influenza (Atladottir et al, 2012;Deykin and MacMahon, 1979;Shi et al, 2003;Zhang et al, 2010) in the incidence of ASD. Some studies suggest fever as a correlate (Atladottir et al, 2012), with this risk potentially tempered by anti-fever medications, such as Advil, Tylenol, or Nyquil (Zerbo et al, 2013).…”
Section: Congenital Infectionmentioning
confidence: 99%
“…Given the diversity of infections that show a connection to the spectrum of autism disorders (Boksa, 2010;Libbey et al, 2005), as well as evidence from MIA models that reaction to infection rather than infection itself may lead to autismrelated symptoms (Shi et al, 2003), a possible common etiology may be the influence of the immune system (Gottfried et al, 2015;Lintas et al, 2010;Zhang et al, 2010). Cytokines, small cell-signaling proteins that act as immunomodulatory and endocrine messengers, have been implicated throughout the process of CNS development (Boulanger, 2009;Jones and Thomsen, 2013).…”
Section: Cytokinesmentioning
confidence: 99%
“…106,109,139,140 Two 141,142 of three cohort studies [141][142][143] found a significant association between either prepregnancy weight, pregnancy weight gain or early-life obesity and ASD. A 2009 metaanalysis found a positive association between maternal gestational diabetes and ASD.…”
Section: Parental Agementioning
confidence: 99%
“…157 However, a more recent systematic review 13 indicated mixed findings. Since then, three [158][159][160] of five studies 106,109,[158][159][160] have found a significant association between low birth weight and ASD. In most studies, the low birth weight threshold was 2500 g.…”
Section: Pregnancy Complicationsmentioning
confidence: 99%
“…Dealberto also emphasizes the additional risk of autism to offspring of veiled women. Similarly, Zhang et al have described a "maternal unhappy emotional state" as a risk factor for autism [90]. James has suggested that the association between maternal migration, the accompanying stress, and autism is mediated by high maternal adrenal androgen concentrations [91].…”
Section: Environmental Factorsmentioning
confidence: 99%